Cooperative Effects of FGF-2 and VEGF-A in Periodontal Ligament Cells. (January 2014) - Yanagita, M.; Kojima, Y.; Kubota, M.; Mori, K.; Yamashita, M.; Yamada, S.; Kitamura, M.; Murakami, S.
We previously demonstrated that topical application of fibroblast growth factor (FGF)-2 enhanced periodontal tissue regeneration. Although angiogenesis is a crucial event for tissue regeneration, the mechanism(s) by which topically applied FGF-2 induces angiogenesis in periodontal tissues has not been fully clarified. In this study, we investigated whether FGF-2 could induce vascular endothelial growth factor (VEGF)-A expression in periodontal ligament (PDL) cells and whether cell-to-cell interactions between PDL cells and endothelial cells could stimulate angiogenesis. FGF-2 induced VEGF-A secretion from MPDL22 cells (mouse periodontal ligament cell line) in a dose-dependent manner. Transwell and wound-healing assays revealed that co-stimulation with FGF-2 plus VEGF-A synergistically stimulated the migration of MPDL22 cells. Interestingly, co-culture of MPDL22 cells with bEnd5 cells (mouse endothelial cell line) also stimulated VEGF-A production from MPDL22 cells and tube formation by bEnd5 cells. Furthermore, time-lapse analysis revealed that MPDL22 cells migrated close to the tube-forming bEnd5 cells, mimicking pericytes. Thus, FGF-2 induces VEGF-A expression in PDL cells and induces angiogenesis in combination with VEGF-A. Cell-to-cell interactions with PDL cells also facilitate angiogenesis.